Pengaruh Budaya Organisasi Dan Gaya Kepemimpinan Terhadap Kinerja Guru SMA Negeri 1 Soromandi - Agamawansyah Agamawansyah; Muhammad Yusuf (Manajemen Kreatif Jurnal, 2023)
This research aims to determine the influence of organizational culture and leadership style on the performance of 1 Soromandi High School teachers. Data collection techniques use observation, questionnaires and literature study. The sample in this study was 34 ASN and P3K teacher respondents with the sampling technique being purposive sampling. The data analysis technique uses multiple linear regression analysis. The research results show that both partially and simultaneously organizational culture and leadership style have a significant influence on the performance of teachers at SMAN 1 Soromandi.